2023
DOI: 10.3390/medicina59050828
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Awareness, Perceptions, and Opinions towards Artificial Intelligence among Healthcare Students in Riyadh, Saudi Arabia

Abstract: Background and Objective: The role of the pharmacist in healthcare society is unique, since they are providers of health information and medication counseling to patients. Hence, this study aimed to evaluate Awareness, Perceptions, and Opinions towards Artificial intelligence (AI) among pharmacy undergraduate students at King Saud University (KSU), Riyadh, Saudi Arabia. Materials and Methods: A cross-sectional, questionnaire-based study was conducted between December 2022 and January 2023 using online question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
5
26
1
Order By: Relevance
“…This is similar to findings from studies that investigated attitudes towards the impact of AI in healthcare among pharmacy students in Saudi Arabia and others involving medical and dental students, with 69-90% of the participants indicating positive attitudes, suggesting a shared optimism about AI's potential impact across different healthcare fields. 19,23,24,35,39 Moreover, our results show that most pharmacy students view AI's influence on a pharmacist's daily life positively and favour AI software for second opinions on medical issues. This aligns with previous studies among physicians and medical students, which reported positive views ranging from 62 to 83% on AI's diagnostic accuracy and treatment capabilities.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This is similar to findings from studies that investigated attitudes towards the impact of AI in healthcare among pharmacy students in Saudi Arabia and others involving medical and dental students, with 69-90% of the participants indicating positive attitudes, suggesting a shared optimism about AI's potential impact across different healthcare fields. 19,23,24,35,39 Moreover, our results show that most pharmacy students view AI's influence on a pharmacist's daily life positively and favour AI software for second opinions on medical issues. This aligns with previous studies among physicians and medical students, which reported positive views ranging from 62 to 83% on AI's diagnostic accuracy and treatment capabilities.…”
Section: Discussionmentioning
confidence: 58%
“…(n = 136 out of n = 157) of senior pharmacy students in Saudi Arabia disclosed that they had not received any formal AI training. 35 However, it is crucial to consider the variations in pharmaceutical curriculum systems and geographical and socioeconomic contexts when comparing these results. For instance, in our study, a significant majority of participants were studying in European countries.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also consistent with those of previous studies. 21 , 23 We also enquired about the diagnostic ability of AI compared with the clinical experience of a human doctor; approximately half of the participants agreed that AI would be clinically superior. This has been supported by previous studies that reported that, in radiology and pathology, AI will replace doctors based on diagnostic superiority.…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, a study carried out in Saudi Arabia reported that pharmacy students showed good awareness of AI. Moreover, they reported that the majority of the students had positive perceptions about the concepts, benefits, and implementation of AI [26].…”
Section: Plos Onementioning
confidence: 99%
“…Knowing more about AI and having a favorable attitude towards it increases the likelihood that pharmacy students and faculty members will research and use it in their practice. However, the adoption of AI in pharmacy practice is dependent on various factors, including resource availability, training opportunities, regulatory considerations, technological infrastructure, and institutional support [26,27].…”
Section: Introductionmentioning
confidence: 99%